Frequency of paroxysmal nocturnal hemoglobinuria in patients attended in Belém, Pará, Brazil - Brito Junior,Lacy Cardoso de (2011)
BACKGROUND: Paroxysmal nocturnal hemoglobinuria is a hematological disease with complex physiopathology. It is genetically characterized by a somatic mutation in the PIG-A gene (phosphatidylinositol glycan anchor biosynthesis, class A), in which the best known antigens are DAF (decay accelerating factor or CD55) and MIRL (membrane inhibitor of reactive lysis or CD59). OBJECTIVE: To determine the frequency of paroxysmal nocturnal hemoglobinuria in patients attended at the HEMOPA foundation from November 2008 to July 2009. METHOD: Thirty patients, with ages ranging from two to 79 years old and suspected of having paroxysmal nocturnal hemoglobinuria were examined. All patients were immunophenotyped by flow cytometry for the CD5, CD59, CD16 and CD45 antigens. RESULTS: Paroxysmal nocturnal hemoglobinuria was identified in nine of the thirty patients investigated. Another 3 cases had inconclusive results with CD59-negative labeling only for neutrophils. The highest frequency of paroxysmal nocturnal hemoglobinuria patients (7/9) and inconclusive cases (2/3) were between 19 years old and 48 years old, with a median of 28 years. CONCLUSION: These results show the importance of flow cytometry to identify cases in which patients are deficient in only one antigen (CD59).